Our Kitchen Project helps UMP students - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PEKAN, 7 January 2022 - A total of 600 roti canai were successfully distributed for free to Universiti Malaysia Pahang (UMP) students in the UMP Our Kitchen Project - Students Help Students around the Durham Student Residence, Pekan and the UMP Gambang Mosque.